Labial soft tissue contour dynamics following immediate implants and immediate provisionalization of single maxillary incisors: A 1‐year prospective study. (6th May 2019) - Tian, Jiehua; Wei, Donghao; Zhao, Yijiao; Di, Ping; Jiang, Xi; Lin, Ye
Abstract: Background: Soft tissue dynamics in the esthetic zone are gaining increasing attention in recent years. Emerging intraoral scanning technology allows easier capture of soft tissue contours. Purpose: To quantitatively assess the time‐dependent contour alterations of labial soft tissue following single immediate implants and immediate provisionalization (IIPP) in maxillary incisors via intraoral scanning. Materials and Methods: This was a prospective cohort study. Thirty eligible consecutive patients were included and received immediate replacement of a failure maxillary single incisor. A screw‐retained immediate restoration was delivered for each patient. Subsequently, the anterior maxillary region was scanned by an intraoral scanning system at four time points: preoperation (baseline, BL), 3 months (3 m), 6 months (6 m), and 12 months (12 m). The Standard Tessellation Language files were exported to a dedicated software and superimposed for visual analysis. At 3, 6, and 12 months, the mid‐facial mucosa level (ML) was assessed, and the precise three‐dimensional (3D) configuration of the altered volume was calculated and reconstructed for visual analysis. Furthermore, quantitative analysis of the reconstructed morphology was performed using the following parameters: mean change in thickness (△ d ), mesio‐distal width ( w ), coronal‐apical height ( h ), and horizontal and vertical position of the thickest point represented by coordinates ( x, z ). Result: Twenty‐seven of thirty enrolled patients were finally available for analysis at the 1‐year follow‐up. In general, the frontal view of the reconstructed volume exhibited a crescent shape. The mid‐facial ML change at 3, 6, and 12 months was −0.05 ± 0.36 mm, −0.03 ± 0.32 mm, and −0.24 ± 0.37 mm, respectively ( P  = .012). The mean change in thickness at 3 months (△ d 3m ), 6 months (△ d 6m ), and 12 months (△ d 12m ) was 0.50 ± 0.19 mm, 0.59 ± 0.21 mm, and 0.62 ± 0.22 mm, respectively ( P <.001). At 12 months, nine patients had a △ d less than 0.5 mm. The mean △ d 3 m /△ d 12 m and △ d 6 m /△ d 12 m was 0.81 ± 0.17 and 0.96 ± 0.13. The w, h, x, and z results showed no significant differences during the 1‐year observation ( P  = .126, P  = .324, P  = .635, P  = .263). At 12 months, w, h, x, and z were 11.57 ± 1.77 mm, 6.46 ± 2.01 mm, 0.03 ± 1.43 mm, and 2.16 ± 0.65 mm, respectively. Conclusion: During the 1‐year observation following single IIPP treatment in maxillary incisors, the labial soft tissue contour showed a continuous alteration resulting in a mean change in thickness of 0.62 mm that occurred mainly in the first 3 months and tended to be relatively stable after 6 months, while the crescent‐like shape, width, height, and thickest point position of the alteration volume remained stable after 3 months. No advanced mid‐facial recession was observed.